QUALITY ENHANCEMENT OF THE STREET CORRIDOR TO SUPPORT TOURISM BASED ON URBAN DESIGN CONCEPT IN PEMUDA STREET, MAGELANG CITY - Fauzia, Tasnim Arma; Swasto, Deva Fosterharoldas (Jendela Inovasi Daerah, 2024)
Pemuda Street is a corridor in the Magelang Chinatown area, known as one of the shopping centers in Magelang City. This area is generally a commerce and service area consisting of shops, healthcare facilities, and banking services. Despite its dominance by various economic opportunities and claims to be a Chinatown area, it requires a suitable area identity. Problems arise from various perspectives, such as pedestrian facilities being limited to pedestrians with unattractive visual appeal that fails to represent the distinctive characteristics of Chinatown. Consequently, motorcycle riders tend to utilize pedestrians more than walkers. Furthermore, most shops have experienced a decrease in visitors, influencing the economic earnings of the area. The Pemuda Street corridor aims to be planned using the design thinking method, adapting the concept of complete streets with elaboration from the concepts of commercial street, shared street, urban tourism, and vernacular settlement, to address various issues. The planning process begins with problem analysis and literature review to manifest the ideal planning concept. It concludes with creating a master plan design for the area summarized in textual explanations, two-dimensional images, and three-dimensional frameworks. The results of this research is apply the "complete street" planning concept can become the basis for designs that focus on functionality, aesthetics, sustainability, social needs, environmental harmony, and economic progress while respecting the historical values of the area Chinatown in Magelang City.